ANALISIS HARGA POKOK PRODUKSI DALAM PENENTUAN HARGA JUAL UNTUK PENCAPAIAN TARGET LABA PT SEMILA BORDIR DENGAN METODE FULL COSTING - Siti Rohmatul Janah; Febby Maharani; Fahrun Anggraini; Indah Dwi Pangesti; Wanda Desti F (Universitas Tulungagung, 2023)
The objective of the study is to examine the calculation of the estimated cost of manufacturing used at PT SEMILA EMBROIDERY and how it affects the company's selling price. It is hoped that this research will provide insight for the company and help make decisions for the company's progress, especially in terms of determining the estimated cost of the manufacturing process in relation to setting the selling price. Based on the above problems, a hypothesis is proposed that